Monetary Regimes and the Co-Ordination of Wage Setting - Steinar Holden (Center for Economic Studies and ifo Institute (CESifo), 2001)
International comparisons show that countries with co-ordinated wage setting generally have lower unemployment than countries with less co-ordinated wage setting. This paper argues that the monetary regime may affect whether co-ordination among many wage setters is feasible. A strict monetary regime, like a country-specific inflation target, to some extent disciplines wage setters, so that the consequences of uncoordinated wage setting are less detrimental than under a more passive monetary regime (eg a monetary union). Thus, the gains from co-ordination are larger under a passive regime. Under some circumstances a passive regime may induce co-operation in wage setting, and thus lower unemployment, when a stricter regime would not.
Keywords: 330; Wage setting; co-ordination; equilibrium unemployment; monetary regime; monetary union; wage moderation